Safe handoff practices and improvement of communication in different paediatric settings - Pedro J. Alcalá Minagorre; Araceli Domingo Garau; María José Salmerón Fernández; Cristina Casado Reina; Pilar Díaz Pernas; Ángel Antonio Hernández Borges; Belén Rodríguez Marrodán (Elsevier, 2023)
Inadequate information management, especially during patient handoff, contributes to a large part of health care-related adverse events. The Committee for Quality of Care and Patient Safety of the Asociación Española de Pediatría has developed this document to provide an overview of handover practices in different paediatric care settings (emergency, inpatient, intensive care, neonatal and primary care). It describes resources to achieve safe and effective communication in all these settings, such as standardised handoff tools. It also proposes recommendations for the prevention of medication errors during the handover process, to improve safety in interhospital and intrahospital patient transfer, and to optimise communication and continuity of care in chronically ill and medically complex children. Resumen: El manejo deficiente de información, en especial durante la transferencia o el traspaso de cuidados, contribuye a gran parte de los eventos adversos relacionados con la asistencia sanitaria. El Comité de Calidad Asistencial y Seguridad en el Paciente de la Asociación Española de Pediatría ha confeccionado este documento para ofrecer una aproximación a los procesos de transferencia en distintos ámbitos asistenciales pediátricos: urgencias-emergencias, hospitalización, cuidados intensivos, neonatología y atención primaria. Se describen recursos para lograr una comunicación segura y efectiva en todos estos ámbitos, empleando, entre otros métodos, herramientas estandarizadas de transferencia. Se proponen también recomendaciones para la prevención de errores de medicación durante los procesos de transferencia, la mejora de seguridad durante los traslados y derivaciones entre ámbitos, y también para un mejor traspaso de información asistencial en los niños y adolescentes con enfermedades crónicas y complejidad asistencial.